Distribution and structure of African forest elephant trails in anthropogenic savanna-mosaic forest, Gabon - Nomoto, Mayuko; Akomo-Okoue, Etienne François (Frontiers in Conservation Science, 2025)
IntroductionWith increasing human activities, the area affected by humans increases annually and many wild animals are under threat of extinction. On the other hand, there are serious conflicts between human and many wildlife. In order to mitigate conflicts, it is important to understand how animals perceive the balance of benefits and risks in human-inhabited areas and how they use the land. In this study, we investigated how African forest elephants (Loxodonta cyclotis), which are in serious conflict with humans, use anthropogenic environments by focusing on their trails.MethodsThis study targeted two parameters of anthropogenic environments: vegetation, particularly savannas, which have been maintained by human burning for many years, and population density, particularly in low-density seminatural land. Within Moukalaba-Doudou National Park, Gabon, and an adjacent village, we mapped elephant trails and compared their density and structure between vegetation (forest and savanna) and areas (inside and outside the national park).ResultsIn the forest, only 31.4% of the elephant trails were well-established with exposed ground. In the savanna, the density of elephant trails was lower than that in the forest; however, the trails were narrower and 65% of the trails were well established. This suggests that elephants tend to follow specific routes in the savanna that may help them travel more easily, and that they are perceiving some risks. The density of elephant trails outside the national park was higher, and the trails were wider than those in the national park, suggesting frequent elephant use. This was probably due to the crop fields and mango trees attracting elephants.DiscussionIn the study area, available food may be a greater attractant to elephants relative to the risk of being threatened by humans. The findings show that elephant trail surveys can be carried out inexpensively over a short period of time. Moreover, they can clarify land use by elephant populations, including fine-scale heterogeneous movements.